The Extreme Moral Diversity of Men Convicted of Violence Against Their Partners: Four Profiles Based on the Five Moral Foundations - Vecina, María L. (Journal of interpersonal violence, 2021)
The aim of this study is to identify homogeneous profiles based on the five moral foundations in a sample of 376 men undergoing court-mandated treatment for violently abusing their partners. To understand better the meaning of these new profiles as well as their temporal consistency, the profiles were related to different outcomes of the current psychological treatments, before and after a prescribed one, such as self-deception, moral self-concept, benevolent sexism, and hostile sexism. Results from Latent Profile Analysis and Latent Transition Analysis showed good fit for a four-profile solution. This solution was stable from Time 1 to Time 2, both in terms of the scores on the moral foundations and the participants included in each profile. The participants included in each profile were called “Sacralizers”, “All for one”, “Moral outsiders”, and “Purists”. Comparing with standard samples and consistent with the predictions of the moral foundation theory and the sacredness hypothesis, their scores on the moral foundations were clearly different by excess or defect. Those tending to exaggerate or sacralize the moral concerns (“Sacralizers” and “Purists”) were the most self-deceived, the less hostile sexists, and the ones with the highest moral self-conceptualization. Future research will have to test the role of the moral variables in the psychological treatments and think of strategies to change the importance that men convicted of domestic violence give to the five moral foundations, but at least two strategies seem to be needed: one to reduce the exaggerations and another to increase the deficits of the moral foundations.